Hormonal response to single vs repeated bouts of intensive endurance exercise - Ronsen, O.; Haug, E.; Rasmussen, T.; Pedersen, B. K.; Bahr, R. (Medicine & Science in Sports & Exercise, 1998)
The hormonal response of one versus two endurance bouts of exercise on the same day was compared. Elite athletes (triathlon = 4; speed skating = 5) were measured at rest and during exercise (65% VO2max for 65 minutes on a cycle ergometer). A rest period of three hours was provided between the two test trials. Ss rested in bed when not exercising.